The diet of the Olive Bee-eater, Merops superciliosus, in the Central Highlands of Madagascar. (10th December 2021) - Rajemison, Balsama; Goodman, Hesham T; Goodman, Steven M
Abstract : Regurgitated pellets from the Olive Bee-eater, Merops superciliosus, were collected below a hunting perch in Antananarivo, Madagascar, and used to examine this species' food habits. The diet of this species was largely composed of bees (Apidae, genus Apis ) and the next most common group was wasps (Vespidae). Remains of soft-bodied ticks (Argasidae) were also identified, presumably associated with the consumption of ectoparasites during preening.